Overweight and obesity in public schools children of Fortaleza: an exploratory study - Suyanne Freire de Macêdo; Marta Maria Coelho Damasceno; Adman Câmara Soares Lima; Ana Karine Girão Lima; Hérica Cristina Alves de Vasconcelos; Márcio Flávio Moura de Araújo (Online Brazilian Journal of Nursing, 2009)
The increase of the predominance of weight excess among children has been considered a world epidemic which contributes for the development of chronic diseases. This study aimed at detecting the predominance of overweight and obesity in public schools children of Fortaleza. It is about a transversal study performed in 12 schools in the period of March to June, 2008. The sample involved 727 children between 6 and 11 years of age. A form was applied in which socio-demographic, weight, height and Body Mass Index data were recorded. 159 (21.9%) of the participants showed weight excess. 15.3% out of these were overweight, 6.6% obese, 7.7% belonged to the female gender and 9.8% were concentrated in the age group between 9 and 10 years of age. There was no statistical significant difference between gender (p = 0.666) and age group (p = 0.171). Considerable weight excess cases were noticed among the child population studied. The present study observed important information that may not only help for the knowledge of those conditions, but also for the performance of intervention strategies intended to fight the incidence of new cases.